1994
DOI: 10.1016/0735-1097(94)90848-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of new coronary atherosclerotic lesions during a 4-year multifactor risk reduction program: The stanford coronary risk intervention project (SCRIP)

Abstract: These data indicate that intensive multifactor risk reduction tends to diminish the frequency of new coronary lesion formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…129 To address this, specialized programs dedicated to simplifying multifactor CV risk reduction have been developed, resulting in significant improvements in clinical outcomes. [130][131][132][133] In spite of this a patient diagnosed with CVD today can be expected to take as many as 5 or more medications to achieve optimal risk reduction. Limited by cost, concerns about compliance, and the potential for drug-drug interaction, some physicians remain skeptical of the benefits derived from this form of CV polypharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…129 To address this, specialized programs dedicated to simplifying multifactor CV risk reduction have been developed, resulting in significant improvements in clinical outcomes. [130][131][132][133] In spite of this a patient diagnosed with CVD today can be expected to take as many as 5 or more medications to achieve optimal risk reduction. Limited by cost, concerns about compliance, and the potential for drug-drug interaction, some physicians remain skeptical of the benefits derived from this form of CV polypharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…The Stanford Coronary Risk Intervention Project (SCRIP) followed 300 men and women with CHD for 4 years, comparing multifactor risk reduction with usual care [47,48]. The intervention group was counseled to consume a low total fat (less than 20%), low saturated fat (less than 6%), low cholesterol (less than 75 mg/d) diet and exercise was also encouraged.…”
Section: Selected Dietary Intervention Trials Using Angiography As Anmentioning
confidence: 99%
“…Evidently, there seems to be a dissociation between the results of angiographic studies and clini cal outcome: lipid-lowering therapy has been shown to reduce the incidence of cardiovascular events with only small changes in coronary anatomy [98,99]. Therefore, it is most likely that treatment of hypercholesterolaemia depletes the lipid core of early atheromatous plaques, and consequently stabilizes these lipid-rich lesions and prevents further compli cations such as intramural haemorrhage and intralu minal thrombosis, an assumption that has been demonstrated in the Canadian Coronary Atheroscle rosis Intervention Trial (CCAIT) and the Stanford Coronary Risk Intervention Project (SCRIP) [28,100].…”
Section: L Plaque Stabilizationmentioning
confidence: 99%